A STUDY ON THE DEVELOPMENT STRATEGY OF CHILD CARE INSTITUTION FOR CHILDREN AGED 0-3 - TAKING A NURSERY INSTITUTION IN SHANDONG PROVINCE AS AN EXAMPLE - XU, Ke; BI, Chuanchen (International Journal of Engineering Technologies and Management Research, 2022)
As the two-child and three-child policies have been universally put into place, China has introduced a lot of policies and measures to optimize birth rate to promote the growth of the new population, Amid policy circumstance, care service for children aged 0-3 has emerged and developed vigorously. However, the number of non-governmental child care institutions is increasing rapidly, and some early education institutions and training institutions have set up child care institutions using existing customer groups, resulting in fierce market competition. In addition, the short development period of infant and child care services in China leads to unsatisfactory service quality and unbalanced supply of service, moreover, in some child care institutions, there are excess children in class, insufficient teachers, high mobility of nursery governess, uneven professional ability of teaching staff, and insufficient hardware facilities, etc. Under the background of the development of A daycare institution in Shandong Province, in this paper, how the institution should seize the development opportunity of this new industry was discussed, and its own development strategy was formulated to base on the fierce market competition and realize sustainable development.